2019
DOI: 10.1002/gj.3532
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of geochemical signatures of komatiites from the greenstone belts of Dharwar Craton, India: Implications for temporal transition and Archean upper mantle hydration

Abstract: Archean ultramafic–mafic magmatism associated with dynamic mantle melting processes represents an integral part of crustal evolution and continental growth. Archean mantle plumes and their high temperature derivatives in komatiitic magmas provide a cornerstone in understanding the thermal and chemical evolution of the early Earth and its mantle. In this study, we evaluate the geochemical characteristics of the temporally distinct Sargur Group and Dharwar Supergroup greenstone belts of Dharwar Craton in souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 149 publications
(357 reference statements)
0
3
0
Order By: Relevance
“…The origin and evolution of Archean granite‐greenstone belts are subjects of immense interest in understanding the mantle processes, crustal growth, and tectonic evolution of the early Earth. Particularly, the volcanic supracrustals of greenstone belts represent magmatic episodes associated with Precambrian terrane accretion, continental lithosphere evolution and crustal growth through subduction–accretion processes, plume–arc cohabitation, plume–craton interactions, and arc–continent collisions (Barnes & Van Kranendonk, 2014; Dostal & Mueller, 2013; Ganguly, Santosh, & Manikyamba, 2019; Ganguly & Yang, 2018; Ghose & Saha, 2018; Manikyamba et al, 2017; Manikyamba & Kerrich, 2012; Ray et al, 2013; Smithies, Champion, Van Kranendonk, Howard, & Hickman, 2005). Mafic magmatism associated with Precambrian Large Igneous Provinces (LIPs; Mc Call, 2003; Rey, Philippot, & Thebaud, 2003; Sylvester, Campbell, & Bowyer, 1997) as exemplified in Black Range Dyke Swarms in Pilbara Craton, Australia (Heaman, 2008; Wingate, 1999), Mackenzie LIP in northwest Canada (Heaman & LeCheminant, 1993; LeCheminant & Heaman, 1989), Garder Province of southern Greenland (Upton, Emeleus, Heaman, Goodenough, & Finch, 2003) and Dalarna complex in central Scandinavia (Soderlund, Elmings, Ernst, & Schissel, 2006; Suominen, 1991), and numerous Phanerozoic equivalents (Coffin & Eldholm, 1994; Heaman, 2008) are characterized by voluminous magmatic pulses in short durations and giant dyke swarms that served as transport systems for mantle‐derived magmas.…”
Section: Introductionmentioning
confidence: 99%
“…The origin and evolution of Archean granite‐greenstone belts are subjects of immense interest in understanding the mantle processes, crustal growth, and tectonic evolution of the early Earth. Particularly, the volcanic supracrustals of greenstone belts represent magmatic episodes associated with Precambrian terrane accretion, continental lithosphere evolution and crustal growth through subduction–accretion processes, plume–arc cohabitation, plume–craton interactions, and arc–continent collisions (Barnes & Van Kranendonk, 2014; Dostal & Mueller, 2013; Ganguly, Santosh, & Manikyamba, 2019; Ganguly & Yang, 2018; Ghose & Saha, 2018; Manikyamba et al, 2017; Manikyamba & Kerrich, 2012; Ray et al, 2013; Smithies, Champion, Van Kranendonk, Howard, & Hickman, 2005). Mafic magmatism associated with Precambrian Large Igneous Provinces (LIPs; Mc Call, 2003; Rey, Philippot, & Thebaud, 2003; Sylvester, Campbell, & Bowyer, 1997) as exemplified in Black Range Dyke Swarms in Pilbara Craton, Australia (Heaman, 2008; Wingate, 1999), Mackenzie LIP in northwest Canada (Heaman & LeCheminant, 1993; LeCheminant & Heaman, 1989), Garder Province of southern Greenland (Upton, Emeleus, Heaman, Goodenough, & Finch, 2003) and Dalarna complex in central Scandinavia (Soderlund, Elmings, Ernst, & Schissel, 2006; Suominen, 1991), and numerous Phanerozoic equivalents (Coffin & Eldholm, 1994; Heaman, 2008) are characterized by voluminous magmatic pulses in short durations and giant dyke swarms that served as transport systems for mantle‐derived magmas.…”
Section: Introductionmentioning
confidence: 99%
“…These studies reflect on the role of plate tectonics during the Paleo-Mesoarchean time frame. Ganguly et al (2019) evaluated the geochemical signatures of komatiites from Mesoarchean Sargur Group and Neoarchean Dharwar Supergroup greenstone belts of Dharwar Craton, corroborated possible proponents for Archean upper mantle hydration and suggested a gradual temporal transition of mantle characteristics during Meso-Neoarchean times. Recently, Pahari et al (2019) have reported U-Pb zircon age and detailed geochemistry of the island arc basalts and Nb-enriched basalts from the Kudremukh greenstone belt of western Dharwar Craton which were erupted at 2498+43 Ma and these are geochemically similar with the Phanerozoic counterparts.…”
Section: Greenstone Belts: Volcano-sedimentary Sequencesmentioning
confidence: 64%
“…The basal terrestrial deposits also provide insights on the Palaeoarchaean fluvial systems. Ganguly, Santosh , and Manikyamba (—this issue) present an overview of the geochemical features of the Sargur Group and Dharwar Supergroup greenstone belts of the Dharwar Craton in southern India. The Mesoarchean–Neoarchean komatiites in Dharwar provide evidence for heterogeneous, hydrated Archean upper mantle trapped by ascending mantle plumes.…”
mentioning
confidence: 99%